Strategies for Resolving Social Conflict in the Labor Collective - Shabanov, Zeynaddin; Shafiyev, Uzeyir; Abdullayev, Kamran; Shabanov, Musennif; Aliyev, Faig (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2025)
Social conflict within labor collectives represents a recurrent phenomenon shaped by contradictions in interests, goals, and authority relations. Drawing on classical and contemporary sociological perspectives, this study examines how conflicts emerge, evolve, and can be effectively resolved in modern enterprises. This research employs a qualitative, literature-based approach through comprehensive analysis of theoretical writings by Parsons, Coser, Dahrendorf, Simmel, and Boulding, complemented by documented organizational studies such as the Hawthorne experiments. The method emphasizes conceptual interpretation, comparative theoretical analysis, and synthesis of conflict dynamics. Findings show that conflicts originate from both structural and psychological factors, including material dissatisfaction, violations of labor norms, personality differences, and unequal authority relations. Interpersonal, intragroup, and intergroup conflicts follow identifiable stages—from latent tensions to escalation and resolution. Trade unions play a critical role in mediating disputes and promoting social partnership. Theoretical convergence indicates that conflict is multifactorial and inherent within organizational systems. When constructively managed, conflict can enhance group cohesion, clarify values, and contribute to organizational development. This highlights the necessity of socio-psychological awareness in modern management.